Exploring Explainable Artificial Intelligence Techniques for Diabetic Retinopathy Detection using Grad-CAM and VGG16 Framework - Marapelli, Bhaskar; Carie, Ch Anil; Ashish, Ashish; Bechoo Lal, Bechoo Lal; Bhaskar, K Aruna (Journal of Neonatal Surgery, 2025)
Since diabetic retinopathy (DR) is one of the main causes of blindness in the world, avoiding vision loss requires early detection. Although deep learning models have demonstrated significant promise in the diagnosis of DR using retinal pictures, they frequently operate as “black boxes,” which means that it is difficult to understand how they make decisions. Particularly when it comes to making important healthcare decisions, this lack of openness may erode confidence in AI-based medical solutions. Our research uses Explainable Artificial Intelligence (XAI) techniques to improve the interpretability of a deep learning model for DR detection in order to overcome this difficulty. We classify retinal images using a pre-trained convolutional neural network called VGG16.To enhance transparency, we incorporate Gradient-weighted Class Activation Mapping (GradCAM), a technique that generates visual heatmaps, highlighting the regions of the image that influenced the model’s decision. By overlaying these heatmaps onto the original retinal images, we provide a clear, visual representation of what the model “sees” when making a classification. Our approach not only improves accuracy but also enhances trust in AI-based DR diagnosis. The accuracy of the VGG16 model was 72%, and Grad CAM successfully identified the crucial regions linked to DR. Deep learning models are simpler to incorporate into clinical practice thanks to these visual explanations that assist medical personnel in validating AI-generated predictions. Our research helps to improve patient outcomes by bridging the gap between interpretability and AI, which increases confidence among healthcare practitioners and makes AI-assisted medical diagnosis more transparent and trustworthy..